Perceptions Of School Life For Middle School Students According To The Variables Of Motivation For Achievement And Support Lessons - Chenna, Mohamed Ridha شنه,محمد رضا; Isaaadi ,Fares اسعادي,فارس (University of Eloued جامعة الوادي, 2025)
Abstract This study aims to know the perceptions of school life for middle school students according to the variables of motivation for achievement (low, high), and support lessons (studying, not studying). We are looking to find out whether there are differences in perceptions of school life according to the variables of motivation for achievement and receiving support lessons. To conduct this study, we relied on the descriptive approach (causal, comparative), where the field study was applied to a proportional, stratified random sample, consisting of 99 male and female students, relying on two questionnaires, the Perceptions of School Life Questionnaire, and the Achievement Motivation Questionnaire by Abdul Latif Khalifa (2006). The data obtained from the field were processed, relying on the Statistical Package for the Social Sciences (SPSS23) program. The following results were reached: - There are statistically significant differences in perceptions of school life due to the variable of motivation for achievement. - There are no statistically significant differences in perceptions of school life due to the variable of receiving support lessons.
Keywords: perceptions; school life; Achievement motivation; support lessons; Intermediate education.